Effectiveness of the Think Talk Write Learning Strategy toward Concept Mastery of Cell for High School Biology Students - Muzakki, Naufal Ahmad; Diana, Sariwulan; Priyandoko, Didik (FKIP Universitas Lampung, 2022)
In cells, many phenomena occur such as metabolism to protein synthesis, these become abstract and cause students to have difficulty understanding them. A good learning experience is needed so that students can understand the concept correctly. One learning strategy that provides a learning experience to discover and understand concepts is the Think Talk Write learning strategy. This study uses a pre-experimental design method. The subjects in this study were students of class XI science at Muhammadiyah 5 Rancaekek high school. Mastery of concepts measured in this study were C1 (memorization), C2 (understanding), C3 (application), and C4 (Analysis). Based on the results of data processing, the pretest value was 47.22 while the posttest value was 65.28. The results of the analysis using the paired sample TTest obtained from the pretest and posttest values of 0.00, this value indicates that sign <α = 0.00 <0.05. Based on the results of the data analysis, it can be concluded that there is an effectiveness of using the Think Talk Write learning strategy on mastery of concepts in cell material. Keywords: think talk write, concept mastery, cell DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1539-1547